Quenching Temperature Monitoring for Hot Press Forming by using Infrared Thermography - Ng, Chuan Huat; Amran, Muhamad Fuad (Research Progress in Mechanical and Manufacturing Engineering, 2020)
Nowadays, Hot Press Forming (HPF) was developed since the 20th century and Malaysia proud to be the first country in South East Asia to implement and apply this advance forming technology into the manufacturing of national cars. High strength steel such as 22MnB5 boron steel was the common material used in manufacturing. After that, the accurate measurement of the temperature field in the transfer where the temperature falls rapidly proves to be difficult due to the limitation of a thermocouple. The infrared thermography could be used for accurate measurement of temperature field. In this project, the quenching process of boron steel in HPF was studied from the other journal. The strength of the blank material was directly affected by the cooling performance of the die. Therefore, the objective of this study was to observe the heat transfer distribution in the quenching of the hot press forming process. Hence, all the data are having been reviewed and analyzed from several journals which are conduct the experiment with infrared thermography. The parameter that involved which is sample images, temperature gradient, and emissivity. There is a total of three different specimens that are using but the infrared thermography will be used as the monitoring temperature. The temperature distribution of the thermography was displayed to observe the changes during the process. The study of the quenching process with the infrared thermography was to ensure and detect the damage during the hot press forming operation. Based on the value collected, the results showed a different colour of contour. From there, the problem can be detected by review the sample images and the temperature gradient.